(untitled) (Advancements in Homeopathic Research, 2022)
Chronic infection with the Hepatitis C virus is one of the leading causes of global morbidity and mortality.Well-diagnosed thirteen cases of chronic Hepatitis C have been treated with homoeopathic medicines at Gaurang Clinic and Centre for Homoeopathic Research, Lucknow (GCCHR) from December 2008 to October 2016. Out of them, viral load was reduced to below detection limit in three cases (23.08%), considerable reduction in viral load was recorded in six cases (46.15%) and four cases (30.77%) did not respond to treatment.